Delicates ebook - Thummler, Brenna (Sheets., 2021)
Marjorie Glatt's life hasn't been the same ever since she discovered a group of ghosts hiding in her family's laundromat. Wendell, who died young and now must wander the earth as a ghost, soon became one of Marjorie's only friends. But when Marjorie finally starts to fit in at school, she begins to worry that if anyone learns about her secret ghost friends, she'll be labeled as a freak who sees dead people. Wendell isn't the only one pushed to the outside, though. Eliza Duncan, Marjorie's classmate at school, is constantly seen as different by Marjorie's new friends, and starts to feel like a ghost herself. Is it worth it to Marjorie to fit in if it means she excludes both Wendell and Eliza? Following the events of Brenna Thummler's first graphic novel, Sheets, Delicates tells a powerful story about what it means to fit in, and those who are left on the outside. It shows what it's like to feel invisible, and the importance of feeling seen.